Comparison of the Cooperative Learning Models STAD and TGT on Learning Activities and Outcomes in Physics for Vocational High School Students on the Topic of Energy and Its Changes - Nurul Fitria; Subiki Subiki; Alex Harijanto (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
The low level of student learning activity is often found in school learning activities, which has an impact on poor learning outcomes. This study aims to examine the significant comparison of learning activities and physics learning outcomes of vocational high school students using the cooperative learning models STAD (Student Teams Achievement Division) and TGT (Teams Games Tournament), as well as to describe student responses after the implementation of both models on the topic of energy and its changes. This research is a true experimental study with a posttest-only control group design. The population in this study consisted of 186 students, and the sample was determined using a cluster random sampling technique. Data collection methods included observation, tests, questionnaires, interviews, and documentation. The classical assumption test used was the normality test, followed by statistical analyses using the Independent Sample T-test and the Mann-Whitney U-test. The results of the analysis of student learning activity data using the Independent Sample T-test showed a Sig. (2-tailed) value of 0.699 > 0.05, while the analysis of learning outcome data using the Mann-Whitney U-test showed a Sig. (2-tailed) value of 0.806 > 0.05. These results indicate that there is no significant difference between the two learning models in terms of their effect on student learning activities and physics learning outcomes. In addition, the analysis of student responses showed that the implementation of the STAD and TGT models received a very good response. Thus, it can be concluded that while there is no significant difference between the two models, both are effective in generating student interest and positive engagement in learning physics.